In vitro anthelmintic efficacy of Acacia nilotica pods on eggs and adult worms of Haemonchus contortus - Zabre, G; Tindano, B; Dicko, A; Bayala, B; Kaboré, A; Belem, A M G; Tamboura, H H (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Gastrointestinal nematodes are major pathologies in small ruminants. The aime of the present study was  to evaluate  the in vitro anthelmintic effect of aqueous and acetone extracts of pods of Acacia nilotica on the eggs and adult worms of Haemonchus contortus. Eggs and worms were exposed to five increasing concentrations (1.25; 2.5; 5; 10 and 20 mg/mL). The results showed dose-dependent ovicidal (P
Keywords: Acacia nilotica; Anthelmintic; Gastrointestinal nematodes; Haemonchus contortus